From flower to fruit: fruit growth and development in olive (Olea europaea L.)—a review - Rosati, Adolfo; Lodolini, Enrico Maria; Famiani, Franco (Frontiers in Plant Science, 2023)
The olive (Olea europaea L.) is the most cultivated tree crop in the Mediterranean and among the most cultivated tree crops worldwide. Olive yield is obtained by the product of fruit number and fruit size, therefore understanding fruit development, in terms of both number and size, is important, both commercially and scientifically relevant. This article reviews the literature on fruit development, from the flower to the mature fruit, considering factors that affect both fruit size and number. The review focusses on olive but includes literature on other species when relevant. The review brings the different factors affecting different phases of fruit development, addressed separately in the literature, under a single frame of interpretation. It is concluded that the different mechanisms regulating the different phases of fruit development, from pistil abortion to fruit set and fruit size, can be considered as different aspects of the same overall strategy. That is, adjusting fruit load to the available resources, while striving to achieve the genetically determined fruit size target, and the male and female fitness targets.This is a provisional file, not the final typeset article fruit development, from bloom to ripe fruit, and thus fruit size, including factors affecting fruit number.Fruit size results from the interaction of environmental factors and the fruit growth potential, which is genetically determined. The olive fruit is a drupe: a fruit in which the mesocarp and endocarp tissues represent the major part proportion of the fruit (King, 1938). In olive, fruit size is genetically controlled (Padula et al. 2008), differing many folds among different cultivars (Barranco 1999). In general, fruit size differences within and among cultivars can be explained by different cell number, cell size and/or intercellular space (Bertin et al., 2002; Corelli-Grapadelli, 2004). In olive, genotype differences in fruit size are mostly due to cell number (